Prediction of Gas-Liquid Equilibria of CO2-K2CO3-MDEA-H2O System by Electrolyte UNIQUAC Model - Saidah Altway; Kuswandi; Ali Altway (Institut Teknologi Sepuluh Nopember, 2014)
Carbon dioxide is an acid gas that can be harmful impurity especially in the chemical industry. Various processes have been developed to reduce the CO2 from the gas stream. Chemical absorption is the most economical method for CO2 separation. One of the processes that is widely used in industries is Benfield process with K2CO3 (potassium carbonate) as a solvent and amine as a promotor. In this study, MDEA (Methyldiethanolamine) is used as a promotor. As a reference for designing CO2 absorption/stripping packed column in industries, gas-liquid equilibrium data were required. The objective of this study is to predict the gas-liquid equilibria of CO2-K2CO3-MDEA-H2O system at 30oC and atmospheric pressure with 30% K2CO3 and variation of weight percent of MDEA 2, 5, 8, and 10%. The model used in this study is an electrolyte UNIQUAC. The simulation was conducted using Matlab programming. The deviation of predicted CO2 partial pressure with the experimental data is 14.85%. The energy interaction parameters of electrolyte UNIQUAC model were obtained from fitting with the experimental data by Least Square method. The results of this study represented that with increasing CO2 partial pressure, CO2 loading increased, and also at the same partial pressure of CO2, CO2 loading increased with the increase of weight percent of MDEA